IPSA RC20 Meeting at the 12th Congress of the French Association of Political Science: a Brief Overview of the Event - K V Batygin (RUDN Journal of Political Science, 2014)
The article presents an overview of the International Political Science Association (IPSA) Research Committee on Political Finance and Political Corruption (RC20) meeting that was held in Paris on July 9—11, 2013, in the framework of 12 th Congress of the French Association of Political Science. The author focuses his attention on the basic themes of the meeting and presents short commentaries from some of the individual presentations. Special attention is devoted to three keynote papers that contain the most fundamental contentions of the meeting’s participants. The overview also includes information on IPSA.